Potential and Challenges of School-Parent Collaboration in Developing Parental Health Literacy - Kravale, Dace; Kestere, Iveta (Acta Paedagogica Vilnensia, 2024)
The aim of this study is to use the experience of two Latvian schools to outline the potential of school-parent collaboration in promoting parental health literacy by answering the following questions: 1) How is the concept of health literacy understood by parents, teachers, and school administration? 2) What factors limit or hinder school-parent collaboration in promoting health literacy? 3) What are the recommendations of the actors involved to improve school-parent collaboration in promoting parental health literacy? This study adopts a qualitative case study approach and explores two cases of schools in Latvia. The data are obtained from 4 focus group discussions and 2 interviews with 26 respondents, including teachers, parents, and school principals, as well as from school records. The data are processed using content analysis.
Keywords: parental health literacy; health education; health care; collaboration; parents; school